Improving thermal energy storage efficiency of solar collector tanks by placing phase change materials in novel finned-type cells - Isik, Sinem; Yildiz, Cengiz (Elsevier, 2020)
Today, the need for renewable energy sources has been increasing due to the greater than ever depletion of natural energy. Studies on solar energy, which are the most prominent among renewable energy sources, hold the focus of attention. In parallel efforts, here a Phase Change Material (PCM)-based latent heating system is added to hot water collectors to make more efficient use of solar energy. Further to this end, a new type of hot water collector tank with a new finned-type cell structure has been developed. The performance of the newly designed, PCM-loaded finned cell-based tank was compared with that of PCM-loaded nonfinned tank and the standard insulated tank. The results show that the solar energy storage capacity of the newly developed tank increases by approximately 10% more than that of the standard insulated tank and interestingly by approximately 4-5% more than that of a non-finned control tank. This new finned-cell design allowed to keep the water in the tank hot for about 2 h longer than the standard insulated unit. The clear success of both of the PCM-loaded tanks (whether finned or non-finned) over the standard insulated (glass wool) tank stems obviously from the latent heat storage effect of PCM (CaCl2 center dot 6H(2)O). The higher performance of the finned-cell based tank over the non-finned variant, on the other hand, presumably originates from the increased heat transfer efficiency of the former because of the larger surface area provided by the fin effect.
Keywords: Solar energy; Latent heat storage; Phase change material (PCM); Efficiency